AI integration in history education: Perceptions of teachers and students in Palangka Raya - Yudi Susanto; Sari Marselina; Siti Nur Halijah (Indonesian Journal of Educational Development (IJED), 2026)
The integration of artificial intelligence (AI) into history education remains underexplored in peripheral regions of Indonesia, where infrastructure limitations and concerns about cultural representation intersect with the imperative to innovate pedagogy. This mixed-methods study examined teachers' and students' perceptions of AI integration in history learning in Palangka Raya, Central Kalimantan. Participants included 220 Grade XI students and six history teachers from six public senior high schools, selected through purposive sampling for school selection and maximum variation sampling to ensure diversity in socioeconomic background, technological access, and geographic location. Data collection involved a validated 30-item questionnaire measuring five perceptual dimensions (AI understanding, attitudes, readiness, expectations, and barriers), along with 12 in-depth student interviews and six semi-structured teacher interviews. Quantitative analysis revealed moderate AI understanding (M = 3.19), strongly positive attitudes (M = 4.09), moderate readiness (M = 3.28), high expectations (M = 4.10), and awareness of implementation barriers (M = 2.75). Thematic analysis identified strong convergence on AI's complementary role rather than a replacement for human educators. Both groups emphasized concerns about cultural representation and infrastructure constraints. The findings recommend context-responsive AI content co-designed with local communities and equity-focused infrastructure investment to support inclusive digital pedagogy in marginalized regions.